Competitive Advantage and Marketing Performance (A Descriptive Survey on Oil Palm Plantation Industries in West Kalimantan Province) - Nurmala Nurmala; Saniah Saniah; Sy Novieyana; Utin Nina Hermina (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2018)
This research analyzes the competitive advantage in order to enhance the marketing performance of oil palm plantation companies in West Kalimantan Province, which aims to: (1) find out the implementation of competitive advantage of the oil palm plantation companies in West Kalimantan Province, (2) find out the achievement of marketing performance of the oil palm plantation companies in West Kalimantan Province, and (3) find out the influence of competitive advantage on the marketing performance of the oil palm plantation companies in West Kalimantan Province. This is a descriptive and verification research that uses a descriptive and explanatory survey on the analysis unit of oil palm plantation companies in West Kalimantan Province. The period of research implementation of two (2) years, divided into two stages; First Stage (2013) and Second Stage (2014). The data are collected using questionnaires as well as interviews and observations. The collected data are further processed using path analysis. The results of the First Stage (2013) research find that only few of the oil palm plantation companies in West Kalimantan Province are able to achieve the marketing performance in high category or above their expected target. This is presumed to be related to the weak competitiveness or competitive advantage of the companies as found in the results of descriptive analysis of this research. In order to understand more of such relatedness, it is necessary to conduct further research of the Second Stage (2014) focusing on investigating the influence of competitive advantage on the marketing performance of oil palm plantation companies in West Kalimantan Province.